Zinc Micronutrient Deficiency and Its Prevalence in Malnourished Pediatric Children as Compared to Well-Nourished Children: A Nutritional Emergency. (October 2021) - Ahsan, Aliya Kemal; Tebha, Sameer Saleem; Sangi, Rumana; Kamran, Amber; Zaidi, Zain Ali; Haque, Tayyaba; Ali Hamza, Muhammad Syed
Pediatric populations from lower-income countries may experience a higher incidence of zinc deficiency, which may cause physical and neurological dysfunctions. This case control study aims to assess different levels of zinc between malnourished and well-nourished children. Our study included 108 participants, all children less than 12 years of age. Out of the 108, 54 were malnourished children (cases), while 54 were well nourished (control group) and were screened for zinc deficiencies. Zinc deficiencies were 4 times more common in malnourished cases than in controls (OR: 3.89 95% CI: 1.1-14.9) with median value of zinc in cases being 91.69 and that of controls was 117.6. Our findings indicate significant deficiencies in malnourished children as compared to well-nourished children. Additionally, our findings support literature surveyed that suggest dietary changes alone would not be able to replenish zinc levels in children.